Thermodynamic substantiation of the direction of nonequilibrium processes in triadconjugations of machine parts based on the principles of maximum and minimum entropy - Aulin, V.V.; Lysenko, S.V.; Hrynkiv, A.V.; Holub, D.V. (Problems of Tribology, 2022)
The article gives a thermodynamic substantiation of the direction of nonequilibrium processes in tribocouples of machine parts, in tribosystems, based on the principles of maximum and minimum entropy. It is clarified how nonequilibrium processes can be substantiated on the basis of the minimum and maximum function of entropy production: linear and nonlinear nonequilibrium processes and their different thermodynamics. The entropy production function is considered as a function of thermodynamic force flows and thermodynamic flows. The theory of nonequilibrium processes is based on the Liouville equation for classical tribosystems, taking into account external influences or perturbations. It is shown that in thermodynamic processes in tribosystems the principle of entropy maximization is realized as the second principle of synergetics.